1994
DOI: 10.1002/dir.4000080306
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions of mail/phone order shopping media

Abstract: A survey of 980 consumers, measured perceptions of five mail/phone order shopping media-magazines. newspapers, television, direct mail, and catalogs. versus retail store shopping-on eight image dimensions: economical, enjoyable, easy, fast, convenient, sensible, practical, and safe. Image profiles differed significantly among media and between them and store shopping, and among demographic categories. Ratings differed significantly by image dimension, which also interacted significantly with media and store sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Settle et al (1994) examined customer attitude toward mail and phone order shopping, finding that female customers have a more positive attitude than male customers, but attitudes were not influenced by age. Rogers' (1996) longitudinal US study examined trends in direct mail marketing.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Settle et al (1994) examined customer attitude toward mail and phone order shopping, finding that female customers have a more positive attitude than male customers, but attitudes were not influenced by age. Rogers' (1996) longitudinal US study examined trends in direct mail marketing.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…The evaluation process made by the consumer in order to estimate if the incoming direct mail might be valuable and of interest is an important component of the direct mail treatment. The mental calculation (Thaler, 1985) made by consumers to estimate their gain and loss in processing direct mail has been underlined by several researchers (Gehrt, Yale and Lawson, 1996;Settle, Alreack and McCorkle, 1991). They particularly show how the motivation behind direct mail patronage can be broken down into three dimensions (time, space, and effort evaluation) compared with traditional shopping or other alternatives.…”
Section: Response To Direct Mail: a Multidimensional Modelmentioning
confidence: 99%
“…Indeed, in previous studies performed by the Sales and Manager Canada Publication (1991) and Direct Marketing (1998) or Rogers (1990), two thirds of the customers like the direct mail they receive, read it and judge it as interesting and relevant. Moreover, Settle, Alreack and McCorkle (1991) introduced two items in their scale to measure the degree of consumers' direct mail liking showing the importance of the affective rating of direct mail for the customer. Barry (1991) also suggested that Canadian consumers like the fact that direct mail helps them save money or get a good value for their money and that it is an excellent source of information about upcoming innovations and market changes.…”
Section: Response To Direct Mail: a Multidimensional Modelmentioning
confidence: 99%
See 2 more Smart Citations